A análise econômica do direito e o uso da curva de Laffer na efetivação do direito fundamental à vedação do confisco tributário - Oliveira Junior, Raimundo Frutuoso de (2011)
The increasing social demand from governments require increased financial resources to deal with these expenses. Thus, it is necessary to brake the voracious collecting of tax assets not within the mandate of the contributors and do not cause a paralysis of economic activity. The principle of sealing the confiscation tax was established in article 150, IV of the Constitution as a form of protection for taxpayers against these excesses. However, there are doubts about the concept and scope of tax forfeiture, as well as to their status of fundamental rights and and its implementation in practical terms through tax policies formulated by the tax administration. Within this framework, the Laffer Curve is presented as a contribution of economics to be implemented tax policies that have as their objective the efficient economical and tax. It is an economic theory that proposes the existence of a cause and effect relationship between the increase in the taxes paid and tax revenue growth, as rising rates lead to increases in revenues to a certain point, and, thereafter, possible rate increases will lead to a decrease in tax revenue. Such knowledge with the help of the Economic Analysis of Law can generate the proposition that fiscal policy effect the application of sealing the tax forfeiture. The Economic Analysis of Law is a doctrinal movement born in the United States which is the biggest novelty of the Law, since the advent of the Pure Theory of Law by Hans Kelsen. Spread around the world and has applications in various fields of Law. Thus, the overall goal of this dissertation is to investigate the Economic Analysis of Law and the Laffer Curve as a means for ensuring the fundamental right to confiscate tax seal. Methodology used is bibliographical, descriptive and exploratory, also resorting to case law studies. The interdisciplinary approach in developing this proposed study is likely to achieve practical success, as it seeks to connect elements of economics and law in order to design a light and guidance in a tortuous path to realization of the fundamental right concerned by the administration tax, but is relevant for not being more in-depth empirical studies on this theme.